A Compendium of Dangerous Speech: A Case of X Discourse of Zimbabwean Political Actors - Peter Junior Tshetu; Heike Tappe (UIN Salatiga, 2026)
This study investigates dangerous speech on X (formerly Twitter) within Zimbabwe’s polarized and volatile digital political landscape, where recurring electoral tensions, historical grievances, and online political contestation shape discursive practices with potentially harmful societal consequences. Addressing a significant gap in scholarship on Zimbabwe, the study compiles, defines, and critically analyzes forms of dangerous speech produced by eight key political actors together with their followers representing diverse segments of the country’s political ecosystem. Grounded in a descriptive qualitative methodology, the research employs Susan Benesch’s Dangerous Speech Framework (DSF) as its principal analytical lens, while extending its explanatory reach through linguistic structuralism, critical discourse analysis, and the Integrated Model for Monitoring and Prevention (IMMP). Through syntagmatic and associative meaning analysis, the study examines how dangerous meanings emerge not only from explicit lexical choices but also from historical memory, contextual cues, political timing, and digital affordances specific to X. Findings reveal two dominant categories of dangerous speech, namely Moderately Dangerous and Extremely Dangerous expressions, with the latter encompassing historically loaded terms, militant slogans, and mobilizing hashtags that intensify hostility and create conditions conducive to radicalization over time. The study demonstrates that the dangerousness of speech is profoundly context-dependent and cannot be adequately interpreted outside local cultural, historical, and political realities. In refining the DSF’s treatment of political climate, temporality, and platform dynamics, the research advances the framework’s applicability to contemporary online environments and contributes to broader debates on monitoring, interpreting, and preventing dangerous speech in fragile democracies.